Job strain and informal caregiving as predictors of long-term sickness absence: A longitudinal multi-cohort study - Mortensen, Jesper; Dich, Nadya; Lange, Theis; Alexanderson, Kristina; Goldberg, Marcel; Head, Jenny; Kivimäki, Mika; Madsen, Ida EH; Rugulies, Reiner; Vahtera, Jussi; Zins, Marie; Rod, Naja Hulvej (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'The aim of this study was to investigate the individual, joint and interactive effects of job strain and informal caregiving on long-term sickness absence with special attention to gender differences. ' ' METHODS ': 'The study comprised a prospective cohort study of 6798 working adults from France, 14 727 from Finland, and 5275 from the UK. A total of 26 800 participants, age 52 (interquartile range 47–56) years participated in the study. Job strain was assessed using the demand–control model. Informal caregiving was defined as care for a sick, disabled, or elderly person. Long-term sickness absence spells defined as absence >14 consecutive days were registered during two years follow-up. We used recurrent-events Cox regression in random-effects meta-analyses. ' ' RESULTS ': 'A total of 12% men and 21% women had ≥1 long-term sickness absence spell. Among women, both high job strain [hazard ratio (HR) 1.08, 95% confidence interval (95% CI) 1.00–1.17] and informal caregiving (HR 1.13, 95% CI 1.04–1.23) were associated with a modestly higher risk of sickness absence. Women doubly exposed to high job strain and informal caregiving also showed a moderately higher risk of sickness absence (HR 1.20, 95% CI 1.03–1.41), but the excess risk was not more than expected from joint exposure to caregiving and job strain. Neither job strain nor informal caregiving predicted sickness absence for men. ' ' CONCLUSIONS ': 'High job strain and informal caregiving predicted long-term sickness absence among women. However there was no noticeable interaction in the presence of both exposures.
Keywords: gender difference; informal caregiving; interaction; job strain; long-term sickness absence; multi-cohort; predictor; sick leave; sickness absence; unpaid care; women